The Effect of Work-Family Conflict on The Work Stress of The State Civil Apparatus with Locus of Control as Moderation - Yuwono, Wiji; Qomari, Ika Nurul; Nuryakin, Nuryakin (LP3M Universitas Putra Bangsa, 2023)
This study aimed to examine the role of personality factors, locus of control, as moderation in the relationship between work-family conflict and stress. Researchers hypothesize that the internal locus of control may weaken the effect of work-family conflict on work stress. The sample of this study was taken from 110 employees of the Personnel Bureau of the Ministry of Health. The data taken is primary data collected by distributing questionnaires to respondents who have been selected. The practical implications of this study can provide insight to leaders in the Ministry of Health about the effect of work-family conflict on the stress level of workers so that the results of the study can be considered to reduce the influence.